Analisis Ekonomi Syariah dalam Praktik Jual Beli Panen Padi di Kelurahan Klemunan Kabupaten Blitar - Solikhatul Azizah; Imam Mukhlis (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Buying and selling is an economic activity that cannot be separated from daily life. Basically the law of buying and selling in Islam is permissible. Islam has regulated all provisions related to buying and selling activities, but in its implementation there are still irregularities found, one of which is bond trading which contains an element of taghrir (uncertainty) in its implementation. Such buying and selling is still taking place in Klemunan Village, Wlingi District, Blitar Regency. This study aims to determine the mechanism of implementing the system of buying and selling rice harvests in Klemunan Village in terms of an Islamic economic perspective and the reasons why farmers choose to use the system in buying and selling agricultural crops. This research is a case study qualitative research. Data was collected through interviews, observation and documentation. The results showed that the sale and purchase of crops carried out with the slashing cengkalan system which took place in Klemunan Village, Wlingi District, Blitar Regency, East Java, was included in the bonded sale and purchase system. The buying and selling system applied contains an element of market distortion in the Islamic economy, namely taghrir in quantity. The ongoing buying and selling activities with this system are driven by several things, including the area of arable land, practicality, compatibility with buyers, and habits and lack of religious knowledge. Keywords: rice farming; ijon system; transaction; Islamic economics